Validasi Metode Penetapan Kadar Asetosal dan Dipiridamol Menggunakan Metode Spektrofotometri UV Persamaan Simultan - Mutiara, Parmita, Dedi Hanwar, M.Si., Apt (2017)
Dipyridamole and aspirin are an antithrombotic toreduce thrombosis in patients with thrombotic diseases. Both of these compounds can be combined into a single dose that can be determined byUV spectrophotometric method with simultaneous equations. This research was important because this method can be used as an alternative method for routine inspection due to relatively simple, inexpensive, and fast. The purpose of this study was to validatespectrophotometric method with simultan equation to determination aspirin and dipyridamole. Samples were dissolved using mixture of aquabidest and methanol (1:1). The absorbance of samples were observed at 275.5 nm and 292.5 nm. Validation parameters determined were accuracy, precision, and LOD and LOQ. The results from linearity were shown correlation coefficient (r),for acetosal were 0.996 and 0.999 and dipyridamole were 0.998 and 0.999. RSD of repeatability and precision for acetosal were5.92 % and 11.74 %, and dipyridamole were3.78 % and 6.85 %.Recoveryand RSD of accuracy for aspirin were 124.61% and 13.57 % and dipyridamole were 91.52%and 5.85 %. LOD and LOQ value for acetosal compound, at λ 275.5 nm were 58.52 µg/mL and 177.32 µg/mL, whereas at λ 292.5 nm were 18.59 µg/mL and 5.35 µg/mL. LOD and LOQ for dipyridamole at λ 275.5 nm were 6.93 µg/mL and 21.00µg/mL, while at λ 292.5 nm were 4.39 µg/mL and 13.32 µg/mL.The results of the validation method still needs to be optimized because accuracy not meet requirement.